Civil Uprisings in Modern Sudan The 'Khartoum Springs' of 1964 and 1985 - Berridge, W. J. (Bloomsbury Academic, 2015)
In the wake of the protests that toppled regimes across the Middle East in 2011, Sudanese activists and writers have proudly cited their very own 'Arab Springs' of 1964 and 1985, which overthrew the country's first two military regimes, as evidence of their role as political pioneers in the region. Whilst some of these claims may be exaggerated, Sudan was indeed unique in the region at the time in that it witnessed not one but two popular uprisings which successfully uprooted military authoritarianisms. Civil Uprisings in Modern Sudan provides the first scholarly book-length history of the 1964 and 1985 uprisings. It explores the uprisings themselves, their legacy and the contemporary relevance they hold in the context of the current political climate of the Middle East.